Auto‐immune lymphoproliferative disorder and other secondary immune thrombocytopenias in childhood12. Issue 1 (25th October 2012) - Price, Victoria
Abstract Primary immune thrombocytopenia (ITP) in childhood, typically presents as an acute self‐limiting illness. However, secondary ITP is often a chronic disorder due to an underlying disease. Combined cytopenias in childhood, that is, secondary ITP occurring with auto‐immune hemolytic anemia and/or auto‐immune neutropenia, are often associated with disorders characterized by immune dysregulation. Such disorders include systemic lupus erythematosus, auto‐immune lymphoproliferative syndrome, and common variable immune deficiency. Evans syndrome describes the combination of ITP, autoimmune hemolytic anemia, and/or autoimmune neutropenia. However, it is now clear that some patients with Evans syndrome have an underlying immunodeficiency. This report focuses on combined auto‐immune cytopenias and highlights the challenges in their diagnosis and management. Pediatr Blood Cancer 2012; 60: S12–S14. © 2012 Wiley Periodicals, Inc.